Small-scale farmers’ intentions to carry out conservation-oriented agriculture through participation in the Entry-Level Stewardship Agri-Environment Scheme : the role of attitudes and values in farming behaviour - Gallagher, Andrew (SLU/Dept. of Urban and Rural Development, 2018)
This thesis investigates the attitudes of small-scale farmers towards conservation-oriented farming as prescribed through the Entry-Level Stewardship Agri-Environmental Scheme. It aims to understand whether values and identity play a role in how agricultural practices are perceived by farmers and whether this affects their behavioral intentions. The research relates to an ongoing discussion in what is referred to as an ‘agricultural transition’, where in recent decades national and supranational agricultural policy has shifted its support away from productivist-style farming towards agriculture that is increasingly environmentally conscious. Using the Theory of Planned Behaviour, this thesis investigates whether these policy transformations have translated into changing attitudinal and value positions, which centralise the importance of the environment and the provision of public goods. While the farmers presented pragmatic attitudes towards farm management, in line with traditional productivist agriculture based on economic motivations, an awareness of environmental externalities are present within their behavioral intentions to some extent. A diverse range of attitudes were present in the data, however, farmers in general presented positive attitudes towards ELS participation.